The Role of Common Ground on Object Use in Shaping the Function of Infants’ Social Gaze - Dimitrova, Nevena (Frontiers in Psychology, 2020)
The ability to communicate intentionally begins when infants start referring to external objects. Although social gaze has specific communicative functions, it remains unclear what they are. Beyond dyadic—infant-parent—emotional sharing, infant social gaze within the infant-parent-object triad becomes an increasingly complex communicative modality. We argue that the communicative function of infant social gaze is driven by the knowledge shared between the infant and the parent on the referent of the social gaze, namely the object. Although objects have affordances, they are used in conventional ways shared between users (i.e. common ground). Parents transmit to infants the conventional use of objects, which infants progressively learn and master. Accordingly, we hypothesize that within triadic interactions, the communicative function of infant’s gaze toward the parent is shaped by the degree of common ground shared between the two communicative partners on the conventional use of the object. Based on three prototypical vignettes of mother-infant joint toy play sessions of one 8 month-old child and of two 16 month-old children, we provide a qualitative analysis of the function of infant gaze based on 1) infant’s mastery of the conventional use of the toy, and 2) the parental response to the infant’s gaze. Analyses of gaze patterns reveal that when infants do not master object’s conventional use, parents do not interpret infant’s gaze as meaningful. Conversely, when the infant masters object’s conventional use and thus shares with the parent common ground about the object, parents more likely interpret infant’s gaze as meaningful. Our findings highlight the key role that socio-materiality plays in early communicative development. Namely, when referring to objects for which the infant and the parent share common ground, the function of infant’s social gaze becomes communicatively meaningful for the parent. The knowledge on the communicative referent (i.e. the object) shared between the infant and the parent shapes the course of communicative behavior, constitutes and reflects the interactive function of gaze, and cues parents into tailoring their communicative response according to infant’s developmental needs, which in turns feeds back into infant’s learning and development.